URBAN FORM AND GREEN SPACE ALLOCATION: A PATHWAY TO GREEN SOCIAL EQUITY IN SHRINKING CITIES - Mohanad Mohammed Sufyan Ghaleb; Shaxnoza Abdulhaeva (Operational Research in Engineering Sciences: Theory and Applications)
With the recognized significance of urban green space equity in the promotion of public health and environmental sustainability, Saudi Arabian cities face disparities in green space distribution due to urban form variations. Unequal access to green spaces strangely affects lower-income communities which is ruining social and environmental inequalities. Addressing these disparities, the research examines the impact of urban form dimensions on urban green space (UGS) equity in Saudi Arabian cities. Researchers employed the quantitative research approach, utilizing panel data from 15 Saudi Arabian cities over the period 2014-2024. Fixed-effects and random-effects econometric models were applied to assess the relationship between urban form indicators and UGS equity. The results indicate that urban population growth, per capita income, and unemployment rate, public transport coverage positively significantly increase UGS inequities. While, higher population density, vacant land rate, house affordability index, and green space coverage significantly negatively impact UGS equity which highlights the challenges faced by shrinking cities in maintaining accessible green spaces. The study results highlighted that policymakers should integrate green infrastructure development with urban planning strategies that ensure equitable access to green spaces across income groups. Furthermore, enhancing public transport connectivity to parks, repurposing vacant land for community green spaces, and adopting inclusive planning frameworks can significantly improve UGS equity. This study filled a critical gap in the literature by examining the intersection of urban form and UGS equity in Saudi Arabia. It provides novel insights into the role of urban shrinkage, economic disparities, and spatial planning in shaping sustainable urban green space distribution.